Fungal Burden and Raised Intracranial Pressure Are Independently Associated With Visual Loss in Human Immunodeficiency Virus-Associated Cryptococcal Meningitis. (5th February 2021) - Molloy, Síle F; Ross, Brad; Kanyama, Cecilia; Mfinanga, Sayoki; Lesikari, Sokoine; Heyderman, Robert S; Kalata, Newton; Ellis, Jayne; Kouanfack, Charles; Chanda, Duncan; Temfack, Elvis; Lakhi, Shabir; et al.
Abstract: Among 472 patients with human immunodeficiency virus-associated cryptococcal meningitis, 16% had severe visual loss at presentation, and 46% of these were 4-week survivors and remained severely impaired. Baseline cerebrospinal fluid opening pressure ≥40 cmH2 O (adjusted odds ratio [aOR], 2.56; 95% confidence interval [CI], 1.36–4.83; P = .02) and fungal burden >6.0 log10 colonies/mL (aOR, 3.01; 95% CI, 1.58–5.7; P = .003) were independently associated with severe visual loss.